Pengaruh Dukungan Keluarga dan Dukungan Sosial Masyarakat Terhadap Penurunan Risiko Residivisme Melalui Program Pembinaan Kepribadian Pada Narapidana di Lapas Serang - Prihambodo Dwi Prasongko; Tata Rustandi; Udin Suadma (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Recidivism is an important indicator in assessing the effectiveness of the correctional system and the success of inmate rehabilitation programs. The high rate of repeat offenses indicates that the process of rehabilitating and social reintegrating inmates has not been fully optimized. This study aims to analyze the influence of family support and community social support on reducing the risk of recidivism through the Personality Development program for inmates at Serang Penitentiary. This study uses a quantitative explanatory approach with a survey method. Primary data were obtained by distributing questionnaires to 130 inmates selected using a purposive sampling technique. Data analysis was conducted using the Partial Least Square–Structural Equation Modeling (PLS-SEM) method to test the direct and indirect relationships between variables. The results show that family support and community social support have a positive and significant effect on the Personality Development program. The Personality Development program has also been shown to have a significant effect on reducing the risk of recidivism. In addition, the development program acts as a partial mediating variable in the relationship between social support and reduced risk of recidivism. The R-square value of 0.821 indicates that family support, social support, and mentoring programs explain 82.1% of the variation in the reduction in recidivism risk. This finding confirms that the success of inmate reintegration is not solely determined by mentoring within correctional institutions but is also significantly influenced by family involvement and social acceptance. Therefore, the synergy between correctional institutions, families, and the community needs to be strengthened to sustainably reduce the risk of recidivism.